2015 National Winter Canola Variety Trial - Stamm, Michael; Dooley, Scott J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2017)
The objectives of the National Winter Canola Variety Trial (NWCVT) are to evaluate the performance of released and experimental varieties, determine where these varieties are best adapted, and increase the visibility of winter canola across the United States. Breeders, marketers, and producers use data collected from the trials to make informed variety selections. The NWCVT is planted at locations in the Great Plains, Midwest, northern U.S., and Southeast. Senior Authors: Michael Stamm and Scott Dooley, Deptartment of Agronomy, Kansas State University, Manhattan; Other Contributors: Sangu Angadi and Sultan Begna, New Mexico State University, Clovis; Brian Baldwin and Jesse Morrison, Mississippi State University, Starkville; Tracy Beedy, Oklahoma State University, Goodwell; Jourdan Bell, Texas AgriLife Research and Extension Service, Amarillo; Abdel Berrada, Colorado State University, Yellow Jacket; Harbans Bhardwaj, Virginia State University, Petersburg; Matthew Blair and Daniel Ambachew, Tennessee State University, Nashville; Indi Braden, Southeast Missouri State University, Cape Girardeau; Jack Brown, Jim Davis, and Megan Wingerson, University of Idaho, Moscow; Joshua Bushong, Oklahoma State University, Stillwater; Brian Caldbeck, Caldbeck Consulting, Philpot, Kentucky; Claire Caldbeck, Rubisco Seeds, Philpot, Kentucky; Ernst Cebert, Alabama A&M University, Normal; Gary Cramer, Kansas State University, Wichita; John Damicone and Tyler Pierson, Oklahoma State University, Stillwater; Heather Darby and Sara Ziegler, University of Vermont, St. Albans; Jason de Koff and Chris Robbins, Tennessee State University, Nashville; Dennis Delaney, Auburn University, Auburn, Alabama; Paul DeLaune, Texas AgriLife Research Service, Vernon; Dean Elvin, Marquette, Kansas; Eric Eriksmoen, North Dakota State University, Minot; Andrew Esser, Kansas State University, Belleville; John Gassett, Mitch Gilmer, H. Jordan, and Gary Ware, University of Georgia, Griffin; Todd Higgins, Lincoln University, Jefferson City, Missouri; Johnathon Holman and Scott Maxwell, Kansas State University, Garden City; Kimberly Hunter, USDA-ARS, Temple, Texas; Burton Johnson, North Dakota State University, Fargo; Jerry Johnson and Edward Asfeld, Colorado State University, Ft. Collins; Paul Lange, Conway Springs, Kansas; Kevin Larson, Colorado State University, Walsh; David Lee and Melvin Henninger, Rutgers University, Woodstown, New Jersey; Josh Lofton, Oklahoma State University, Stillwater; Charles Mansfield, Purdue University, Vincennes; Lloyd Murdock and John James, University of Kentucky, Lexington; Jerry Nachtman, University of Wyoming, Lingle; Clark Neely and Daniel Hathcoat, Texas A&M University, College Station; Calvin Pearson, Colorado State University, Fruita; Charlie Rife, High Plains Crop Development, Torrington, Wyoming; Brett Rushing, Mississippi State University, Newton; Dipak Santra, University of Nebraska-Lincoln, Scottsbluff; Robert Schrock, Kiowa, Kansas; Tyler Thomas, Fly Over States Ag Research, Troy, Kansas; Wade Thomason and Steve Gulick, Virginia Tech University, Blacksburg; Calvin Trostle and Jonathan Shockey, Texas AgriLife Extension Service, Lubbock; Dennis West, University of Tennessee, Knoxville.
Keywords: Canola; Kansas; Yield; Environmental factors; Oil